Branding Yields Better Harvest: Explaining The Mediating Role of Employee Engagement in Employer Branding and Organizational Outcomes - Asif Hussain Samo; Suman Talreja; Azeem Akhtar Bhatti; Syeda Aisha Asad; Laiba Hussain (Faculty of Economic and Business, 2020)
Employer branding is an intriguing junction of marketing and human resource management, where the positive intangible perception of the employer makes the organization a valuable. It is antecedents and outcomes have been tried and tested. However, there is a need to empirically test how employer branding lures the employees to perform well and to remain loyal to the employer. This study aimed to find the mediating impact of employee engagement between the relationships of employer branding and performance of the employees and their intention to stay in the companies. By using the structural equation model (SEM), the results revealed the full mediation role of employee engagement in between employer branding and employee performance and their intention to stay. This study implies that the bank needs to induce employees to remain engaged, as, with this, the performance and talent retention will yield.JEL Classification: D23, M31How to Cite:Samo, A. H., Talreja, S., Bhatti, A. A., Asad, S. A., & Hussain, L. (2020). Branding Yields Better Harvest: Explaining The Mediating Role of Employee Engagement in Employer Branding and Organizational Outcomes. Etikonomi: Jurnal Ekonomi, 19(1), 77 – 94. https://doi.org/10.15408/etk.v19i1.12320.